Pendekatan Postcolonialism Terhadap Surat Filemon (Merenungkan Kembali Identitas Onesimus Sebagai Budak Yang Melarikan Diri): Merenungkan Kembali Identitas Onesimus sebagai Budak yang Melarikan Diri - Killa, Maikel Enggelo Eden Killa (Unit Penerbitan Informasi dan Teknologi Sekolah Tinggi Teologi Gereja Kalimantan Evangelis (STT GKE), 2023)
Slavery in the ancient Roman empire was an important reality that contributed to how we interpret the Bible texts that were written at that time. The history of reading Philemon's Epistle has long been colored by interpretations suggesting that Onesimus was a runaway slave who had stolen from Philemon, so he needed Paul to write a letter of reconciliation so that Philemon could receive Onesimus back. However, it turns out that readings like this have direct implications related to the interpretation of colonialism that the